El periódico escolar en el contexto de la pedagogía de los proyectos - Lara Cruz, Gianni (Revista Científica, 2006)
The article speaks of the advantages that it bears the work for pedagogic projects through the school newspaper, for the development of the communicative abilities. It is divided two sections. In the first one, it approaches the existent relationship between the media and the school. Some considerations are made on the ways of assuming the media and the school. Some considerations are made on the ways of assuming the media and the concept, more common, of school newspaper. In the second, the tone is proposing and it exposes a series of recommendations as for the development of the reading snd the writing through the school newspaper. At once, appear aspects of practical order around the edition and to the publication of the means of comunication in the classroom.